ANALISIS PENGARUH REMITANSI, INVESTASI ASING LANGSUNG, IMPOR DAN PERTUMBUHAN EKONOMI DI INDONESIA - Putri, Regina Septriani; Ariusni, Ariusni (Universitas Negeri Padang, 2020)
Abstract : This study examined and analysis the effect of remittances, foreigndirect investment, imports, and economic growth in Indonesia in the long run andshort run. This study using Error Correction Model (ECM) method and using theannual time series data from 1989 to 2018. This study found that: (1) remittancehave an insignificant positive effect on economic growth in the long run and shortrun,(2)foreign direct investment have a significant positive impact on economicgrowth in the long run and short run, (3) import have an insignificant positiveimpact on economic growth both in the long run and short run. To increase theeconomic growth in the future, this study suggests the government to decresingimports of consume goods and increasing the inflow of capital goods, rawmaterial goods, remittances and foreign direct investment.Keyword : Remittance, Foreign Direct Investment, Import, Economic Growth andECM